Witnessing entrepreneurial perceptions and proclivity in university students: Developing a process model. Issue 4 (26th June 2020) - Murray, Alan; Crammond, Robert James
Abstract : Purpose: This paper analyses the transition of university students from initial perceptions of enterprise to potentially heightened levels of proclivity towards creative behaviours and future entrepreneurial activity. Design/methodology/approach: Adopting a positivist approach, an intention-based scorecard survey targeted to two cohorts totalling 75 undergraduate students leading to 150 responses at a Scottish university. These were circulated at start and end sessions of four relevant courses, to establish a measure for self-evaluation with respect to perception and proclivity. Findings: The data gathered from the Entrepreneurial Scorecard emphasised differences in perception and proclivity between the two cohorts, namely creativity, risk-taking, leadership and business aspiration. This re-emphasised the three identified themes: awareness through trait identification; autonomy through developing enterprising skills; and achievement through practicing entrepreneurial activities. This formed the basis for our novel model in supporting the entrepreneurial development of students: The Perception to Proclivity Process Model. Research limitations/implications: This study focusses on a single case and further research within other institutions and domains is encouraged to contextually test the transferability of the two key outputs: the Entrepreneurial Scorecard and the Perception to Proclivity Process Model. Practical implications: The practical output of this research is a novel tool for evaluating entrepreneurial perceptions and proclivity through the scorecard. This study adds to the existing research base around entrepreneurial intention and action whilst providing a new model for a guiding framework for the entrepreneurial student and educator journey. Originality/value: This paper's approach outlines many themes and inherent questions of concern to enterprise educators and university management towards the creation, maintenance, or development of an enterprise course or programme. This research introduces the concepts of entrepreneurial perception and entrepreneurial proclivity, explaining the important role they play in developing students. Additionally, the scorecard has potential for application in a longitudinal context as a means of establishing potential shifts in entrepreneurial perception and proclivity. However, the application is not limited to the scope of higher education, with clear potential to apply this tool and approach within other domains.